The case of the missing moonstone - Stratford, Jordan (Stratford, Jordan. Wollstonecraft Detective Agency, 2016)
Lady Ada Byron and Mary Godwin become best of friends and decide to form the Wollstonecraft Detective Agency. It is a secret agency because they know clients wouldn't trust their secrets to two young girls, and also so their parents don't find out. Their first case involves breaking into and out of a prison, dodging fez-wearing men, telling a few lies, and also pursuing a thief by air balloon.